2015
DOI: 10.1080/09168451.2015.1032883
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feeding outer bran fraction of rice on lipid accumulation and fecal excretion in rats

Abstract: Outer bran fraction of rice (OBFR) contains higher concentrations of crude fiber, γ-oryzanol, and phytic acid compared to whole rice bran (WRB). In this study, we examined the effects of feeding OBFR on lipid accumulation and fecal excretion in rats. Twenty-one male rats at seven-week-old were divided into a control group and two treatment groups. The control group was fed a control diet, and the treatment groups were fed OBFR-or WRBcontaining diet for 21 days. There was no significant difference in growth per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…In addition, although most nutrients are absorbed in the small intestine, some fat does reach the colon. About 5% of dietary fats are excreted in feces, and increased dietary saturated fat or dietary fiber increases fat excretion (115, 116). Colon does have nutrient absorptive capacity (117, 118), and it is possible that diet affects absorption of bacterial products in the colon as well as in the small intestine.…”
Section: Diet Modulates Absorption Of Bacterial Componentsmentioning
confidence: 99%
“…In addition, although most nutrients are absorbed in the small intestine, some fat does reach the colon. About 5% of dietary fats are excreted in feces, and increased dietary saturated fat or dietary fiber increases fat excretion (115, 116). Colon does have nutrient absorptive capacity (117, 118), and it is possible that diet affects absorption of bacterial products in the colon as well as in the small intestine.…”
Section: Diet Modulates Absorption Of Bacterial Componentsmentioning
confidence: 99%
“…In line with this, the study showed the differences in the quantities of some of these bioactive compounds that have hypolipidemic effects. Studies have illustrated that the higher the γ-oryzanol, phytosterols, and fibers present in the rice grain, the better the hypolipidemic effects and the ability to inhibit the enzyme responsible for cholesterol synthesis ( 23 ). Also, an increase in the γ-oryzanol content brought about by germination further lowers the lipid profile of the OVX rats by inhibiting cholesterol absorption in the intestines, and thus also increasing fecal cholesterol excretion ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…A control diet (AIN-93G) and a diet containing 5% OBFR were prepared in advance for use in the study. OBFR was collected as previously described [6]. The crude protein (CP), neutral detergent fiber (NDF), and gross energy (GE) components of the two diets were designed to be equal.…”
Section: Diet Preparationmentioning
confidence: 99%
“…Interestingly, ingesting insoluble fiber has been found to reduce energy digestibility, body weight gain, or blood lipid levels in animals, e.g., feeding a dietary fiber-rich by-product of the soy milk industry to healthy rats for 4 weeks showed decreases in weight gain and serum total cholesterol level [5]. In addition, we previously found that feeding the outer bran fractions of rice (OBFR) to rats for 3 weeks enhanced fecal lipid excretion, and consequently reduced abdominal lipid accumulation [6].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation